Proceedings of Fifth International Conference on Soft Computing for Problem Solving SocProS 2015, Volume 1 - Pant, Millie; Deep, Kusum; Bansal, Jagdish Chand; Nagar, Atulya; Das, Kedar Nath (Advances in Intelligent Systems and Computing,, 2016)
This two volume book is based on the research papers presented at the 5th International Conference on Soft Computing for Problem Solving (SocProS 2015) and covers a variety of topics, including mathematical modelling, image processing, optimization methods, swarm intelligence, evolutionary algorithms, fuzzy logic, neural networks, forecasting, medical and health care, data mining, etc. Mainly the emphasis is on Soft Computing and its applications in diverse areas. The prime objective of this book is to familiarize the reader with the latest scientific developments in various fields of Science, Engineering and Technology and is directed to the researchers and scientists engaged in various real-world applications of 'Soft Computing'.